UJI EFEK HIPOGLIKEMIK KOMBINASI EKSTRAK ETANOL DAUN SAMBILOTO (Andrographis paniculata Nees) dengan AKARBOSE pada TIKUS PUTIH (Rattus norvegicus) TERINDUKSI ALOKSAN - Sukmawati Sukmawati; Muhammad Akbar Harsita; Rachmat Kosman (Fakultas Farmasi UMI, 2016)
Acarbose and sambiloto have the same mechanism of action in lowering blood glucose levels by inhibiting alfaglukosidase enzymes in the gut. This study aims to determine the hypoglycemic effect and combination effect from ethanol extract of sambiloto leaves (Andrographis paniculata Nees) with acarbose in rat (Rattus norvegicus) induced alloxan. Twelve Wistar rats were divided into 4 groups; negative control, positive control, and two treatment groups (EEDS 59 mg/kgBW with Acarbose 2,05 mg/kgBB as combination I and EEDS 234 mg/kgBW with Acarbose 2,05 mg/kgBB as combination II). Diabetes Mellitus was induced by Aloksan Monohidrate dose 135 mg/kg BB for three days. Level of blood glucose was measured with glukometer at 2, 4, 6 and 8 day. Treatment with combinations of EEDS doses 59 and 234 mg/kgBW and Acarbose 2,05 mg/kgBB for 7 days significantly decreased blood glucose level (p<0,05) by 48,97 %, and 58,81 % respectively.